Diagnosis and treatment of male breast cancer. (November 2012) - Constantinou, Chloe; Fentiman, Ian S
SUMMARY Male breast cancer (MBC) accounts for <1% of mammary neoplasia and because of its rarity, diagnosis and treatment is based on breast cancer in women. The PubMed database was searched for all English language articles from 1993 to May 2012. Search terms included: male breast cancer, diagnosis, treatment and management. Although rare, MBC incidence is rising. Risk factors include hormonal imbalance, Klinefelter's syndrome, exposure to radiation and BRCA2 mutations. Clinical evaluation combined with fine-needle aspiration/core biopsy usually suffices for diagnosis, but mammography can be helpful. Modified radical mastectomy was the standard treatment; total mastectomy and sentinel node biopsy is now the treatment of choice in node-negative cases. Tamoxifen is the mainstay of adjuvant hormonal therapy, but a role for aromatase inhibitors is emerging. Given the low incidence of MBC, worldwide studies are needed to improve management and prognosis.